Study of sago starch (Metroxylon sagu) gelatinization by differential scanning calorimetry - Che Man, Yaakob B.; Abd. Ghani, Maaruf B.; Mat Hashim, Dzulkifly B.; Abd. Rahman, Russly (Blackwell Publishing, 2001)
Differential scanning calorimetry (DSC), at various heating rates (1-30C/ min) and water:starch ratios (0.1:1-4:1), was used to study gelatinization phenomena of sago starch. The results showed that the gelatinization temperature and enthalpy (ΔH) of starches in excess water were 60-77C and 15.5-15.8 J/g, respectively. ΔH of gelatinization remained substantially the same at excess water contents, but decreased significantly beyond a water:starch ratio of 1.3:1. A single endothermic transition (G) that transformed into a double endotherm (G and M1) and only M1 occurred, respectively, at excess, intermediate and limited water contents. At 50% water content, evidence of the M1 endotherm was observed, and 85C represented the effective conclusion temperature (Tm) at the end of melting for sago starch. The experimental data were treated thermodynamically by applying an equation describing phase transitions of semi-crystal-line polymers. The calculated value for the melting point of the undiluted polymer (Tmo) was 432 K (R2=0.96).